2021
DOI: 10.48550/arxiv.2105.08043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Proportional Rankings

Abstract: Proportional ranking rules aggregate approval-style preferences of agents into a collective ranking such that groups of agents with similar preferences are adequately represented. Motivated by the application of live Q&A platforms, where submitted questions need to be ranked based on the interests of the audience, we study a dynamic extension of the proportional rankings setting. In our setting, the goal is to maintain the proportionality of a ranking when alternatives (i.e., questions)-not necessarily from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Recent studies address fairness in online versions of other public decision-making problems, such as dynamic proportional rankings [Israel and Brill, 2021] and participatory budgeting [Lackner et al, 2021].…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies address fairness in online versions of other public decision-making problems, such as dynamic proportional rankings [Israel and Brill, 2021] and participatory budgeting [Lackner et al, 2021].…”
Section: Related Workmentioning
confidence: 99%
“…Sonar et al [35] showed that even checking whether a given committee is optimal when using these two rules is hard. Finally, the hardness of problems involving restricted voter preferences and committee selection rule have been studied [36,37] and so has the proportional representation in dynamic ranking [38].…”
Section: Fairness In Ranking and Set Selectionmentioning
confidence: 99%